Detection and Genetic Correlation Analysis of Diarrhea Cases and Norovirus in Oysters in Yantai, China - Sun, Zhenlu; Niu, Peihua; Jin, Miao; Gao, Qiao; Wang, Ji; Ma, Xuejun (Frontiers in Public Health, 2022)
Background: This study aimed to assess the correlation between Norovirus, diarrhea, and raw oysters from eastern coastal areas in Yantai, Shandong, China Methods: Marine oysters were selected from three aquatic markets in Laishan District, Yantai City, in March 2019.Meanwhile, 100 fecal samples from patients with diarrhea from the same areasduringthe same periodwere collected. The nucleic acids of these sampleswereextracted and detected employing RT-PCR for NorovirusGⅠ/GⅡ.TheVP1 gene of coat protein of Norovirus wasamplified by semi-nested RT-PCR and sequenced. TheVP1 sequence comparison was performed with BioEdit software and the evolutionary tree was constructed using Mega7.0 software. Results: Of 151 oysters, 42 (27.8%) were positive for Norovirus. Among them, 32 (21.2%) were GII positive, 10 (6.6%) were GI positive and one GI-VP1 sequence was obtained in oysters samples.Of100 fecal samples of diarrhea patients，38 were GII positive and 17 were GI positive. Totally, 19 GIIVP 1 sequences and 8 GI VP 1 sequences were obtained. TwoG1 VP 1sequencesintwo fecal samples showed 98.7% nucleotidessequence identity and 99.1% amino acid sequenceidentitytoG1 VP 1 acquired inoneoyster sample. Conclusions: These data demonstrated that oysters were responsible for the transmission of the Norovirustohumansin Yantai, Shandong, China.